Autorreificação da imagem e reconhecimento docente - Luiz, Ercília Maria de Moura Garcia (2015)
The present thesis titled Image self-reification and teacher recognition is developed in the Post-graduation Program in Education (PPGE) of the Federal University of Santa Maria (UFSM), in the Research Field Training, Knowledge and Professional Development. The proposed study has as objective to investigate the theoretical way among the question of self-reification of the teacher image and the possibility of transcendence, to then discuss the recognition in the teacher-student inter-subjectivity. To achieve this goal, we opted for the turning of recognition from the perspective of Axel Honneth (2003), heir to critical reflections of the Frankfurt School, establishing a unique position in relation to the problem of reification. In this research, the study design focuses on qualitative approach, hermeneutical way, that involves the heard from implicated individuals, with reference to the comprehension of Gadamar (1998). The critical theory of Adorno and Habermas is used as a parameter to support in the hermeneutics of the Prometheus myth and the teachers narratives. From the emerging data, it places the problematic question: to what extent the turning of recognition of critical theory, especially in the purposes of recognizing the other and language, can help in overcoming the teacher image self-reification in contemporary days? From the perspective of post-metaphysical thinking, the learning, in the teaching/student dialogue, needs not only the cognitive understanding, as this is often frustrated, but especially the desbarbarization of the teacher image, considering the mutual recognition in language. When this happens, the teacher can get stuck to the reifying language and to the impossibility recognition, forgotten and chained as in the myth of Prometheus. As a result, the need to understand the displacement of the self-reification to the recognition, that is preceded by self-realization, which is identified by Axel Honneth (2003) as the ethical attitude. It is proposed, therefore, to find a positive response to the hypothesis that self-recognition of the teacher image occurs by the linguistic ethos as self-maker habit in teacher-student inter-subjectivity.